2006
DOI: 10.1016/j.yqres.2005.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Episodic Late Holocene dune movements on the sand-sheet area, Great Sand Dunes National Park and Preserve, San Luis Valley, Colorado, USA

Abstract: The Great Sand Dunes National Park and Preserve (GSDNPP) in the San Luis Valley, Colorado, contains a variety of eolian landforms that reflect Holocene drought variability. The most spectacular is a dune mass banked against the Sangre de Cristo Mountains, which is fronted by an extensive sand sheet with stabilized parabolic dunes. Stratigraphic exposures of parabolic dunes and associated luminescence dating of quartz grains by single-aliquot regeneration (SAR) protocols indicate eolian deposition of unknown ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 62 publications
0
27
0
Order By: Relevance
“…This young deposit had an OSL age of 36 ± 5 years, giving confidence that this material was well-bleached at deposition. The same presumably applies to the 25 ± 4 years reported by Stokes et al (2004), the 20 ± 2 years reported by Forman et al (2006) and the 10 ±3 years reported by Bristow et al (2007) (see footnote to Table 2). In the first case, the sample was taken at a depth of 70 cm in Mahelian Sahel, in the second, it was aeolian sand sampled near the surface in San Luis Valley, Colorado, USA, and in the third, it was aeolian sand sampled at the surface of a dune in the Namib dessert.…”
Section: Resetting Of the Osl Signalmentioning
confidence: 70%
See 3 more Smart Citations
“…This young deposit had an OSL age of 36 ± 5 years, giving confidence that this material was well-bleached at deposition. The same presumably applies to the 25 ± 4 years reported by Stokes et al (2004), the 20 ± 2 years reported by Forman et al (2006) and the 10 ±3 years reported by Bristow et al (2007) (see footnote to Table 2). In the first case, the sample was taken at a depth of 70 cm in Mahelian Sahel, in the second, it was aeolian sand sampled near the surface in San Luis Valley, Colorado, USA, and in the third, it was aeolian sand sampled at the surface of a dune in the Namib dessert.…”
Section: Resetting Of the Osl Signalmentioning
confidence: 70%
“…Five aeolian depositional events in the past ∼ 1200 years were found in the Great Sand Dunes National Park and Preserve in the San Luis Valley, Colorado by Forman et al (2006). The primary geochronometer was SAR quartz OSL dating (using a 200°C preheat temperature), with Multiple-Aliquot Regeneration (MAR) as a complementary approach (Singhvi et al, 1982;Jain et al, 2003) using sand-sized quartz.…”
Section: Aeolian-inland Depositionmentioning
confidence: 99%
See 2 more Smart Citations
“…3b and c), that may be coincident with episodes of dune reactivation (cf. Marin et al, 2005;Forman et al, 2006Forman et al, , 2008. The PDSI includes parameterization for precipitation, temperature and also incorporates a supply and demand model for soil moisture.…”
Section: Climatic and Geomorphic Contextmentioning
confidence: 99%